Geodiversidade e geoconservação em áreas urbanas : estudo do Morro da Serrinha, em Goiânia, Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This master thesis examined the relevance of the Serrinha Hill Urban Green Area Geodiversity, in Goiânia, Goiás. It presented an extensive theoretical-methodological survey on Geodiversity, concluded with a review of studies on Geodiversity in the State of Goiás. Then, information was gathered about historical, cultural, and physiographic aspects of Goiânia and the Serrinha Hill. Abiotic aspects, land use and urban occupation of the Serrinha Hill and its surroundings were analyzed through digital cartography. In a survey of press news about the Serrinha Hill, facts related to the daily life of this area were identified, such as its occupation by evangelical groups and the process of repossession to the Goiás State. Fieldwork validated information gathered in the bibliography and consulted data, allowing a better understanding of the landscape. At the end of the dissertation, the information collected about Goiânia and Serrinha Hill was revisited in the light of Geodiversity, allowing for an assessment of Geodiversity using Brilha's methodology (2016), conducted through Geossit, a platform for registering Brazilian geosites, maintained by the Brazilian Geological Survey. As a result, it was identified that Serrinha Hill does not have high scientific relevance and cannot be classified as a geosite. However, it presents significant potentials for Geoeducation and Geotourism, being classified as a Geodiversity Site with National Relevance on the Geossit platform. As a consequence of this relevance, geoconservation actions are necessary, which can be supported by geoeducational activities stemming from the structuring of this Urban Green Area.
Geodiversity and geoconservation in urban areas : study of Serrinha Hill, in Goiânia, Goiás
Keywords: Morro da Serrinha, GO; Geodiversidade; Geoconservação; Geoeducação; Serrinha Hill, BR; Geodiversity; Geoconservation; Geoeducation; GEOCIENCIAS::GEOGRAFIA FISICA; GEOGRAFIA FISICA::GEOECOLOGIA